PENYULUHAN TEKNOLOGI INFORMASI DAN KOMUNIKASI BAGI SISWA-SISWI PADA SMA GKPI PADANG BULAN MEDAN - Larosa, Fati Gratianus Nafiri; Rumapea, Humuntal; Manalu, Darwis Robinson; Maslan, Jhoni; Rumapea, Sri Agustina; Sarkis, Indra M.; Hasibuan, Doli; Rumapea, Yolanda Y. P.; Rajagukguk, Edward; Gea, Asaziduhu; Silalahi, Arina Prima; Samosir, Nettina; Aritonang, Mendarissan; Lumbanraja, Posma; Purba, Mufria J. (Universitas Methodist Indonesia, 2023)
Information technology plays a very important role in the world of education, especially when blended learning is carried out, where there is a combination of face-to-face and virtual meetings. In addition, Blended Learning is a part or element of social interaction that grows and develops among students. Face-to-face meetings prioritize direct interaction both gestures or body language, voice intonation and eye gaze. There is strong information technology support that bridges interpersonal interactions, so this also influences the interactions between teachers/educators and students. Practical, eye-catching and easy to carry around, making Laptops or Smartphones a very popular Information and Communication Technology product, Blended Learning is no exception. The applications used are also very easy to install and some are even free, for example Kahoot!, Quizizz, Padlet and Canva.